Freshwater aquarium models : - Tullock, John (Wiley, 2007)
This book shows you step-by-step and fish-by-fish how to create a beautiful, harmonious aquarium that mimics a natural habitat and fosters healthy fish and plant life. It includes more than eighty detailed recipes for aquariums of different types and sizes, specific aquarium model designs, the basics of aquarium setup and maintenance, and a 16-page color catalog of fish and plant varieties.